Answer:
Step #1). Subtract 4 from each side of the equation.

Step #2). Divide each side by 0.3 .

At this point, be careful. The answer will jump up off the paper

into your face.

Step #2). Divide each side by 0.3 .

At this point, be careful. The answer will jump up off the paper

into your face.

Answer:

4+0.3x=19

0.3x=19-4

0.3x=15

x=15/0.3

x=50

Is 2 * 17 5/6 greater than or less than 36? Explain

What is 18x-9(x-1)=5(3x+3)

How do u solve this?

If there are 36 performer's in a dance recital and the ratio of men and women are 2:7.How many of the men where performer's??????????????????????

How many of 26 gallons can go into quarts

What is 18x-9(x-1)=5(3x+3)

How do u solve this?

If there are 36 performer's in a dance recital and the ratio of men and women are 2:7.How many of the men where performer's??????????????????????

How many of 26 gallons can go into quarts

-- Do anything you need to do in order to get 'x' all by itself on one side and everything else on the other side.-- As soon as you do anything to one side of the equation, you must immediately do the same thing to the other side.-- That's the whole book on solving any equation with a single variable.

**Answer:**

24 mm

**Step-by-step explanation:**

Since it is a right triangle, we can use Pythagorean theorem

where a and b are the legs, and c is the hypotenuse.

We know one of the legs is 10, and the hypotenuse is 26, so we can substitute 10 in for a, and 26 in for c.

Solve the exponents

Now, solve for b. To do this, get b by itself.

First, subtract 100 from both sides

Take the square root of both sides

b=24

So, the other leg is 24 mm

**Answer:**

24mm

**Step-by-step explanation:**

I took the Quiz

I believe it's times 12

The remainder theorem says that dividing a polynomial by leaves a remainder of . Here, , then .

When you divide the given **polynomial** by x + 4, the remainder is 0. When you divide by x - 3, the remainder is 428.

To divide the polynomial p(x) = x^4 + 6x^3 + 7x^2 − 6x − 8 by x + 4 and x - 3 using the remainder theorem, first you substitute the roots of the **divisor** into the polynomial.

For x + 4, the root is *-4*. Substituting -4 into the** polynomial yields** p(-4) = (-4)^4 + 6*(-4)^3 + 7*(-4)^2 - 6*(-4) - 8 = 0. Thus, the remainder is 0 when dividing by x + 4.

For x - 3, the root is *3*. Substituting 3 into the polynomial yields p(3) = (3)^4 + 6*(3)^3 + 7*(3)^2 - 6*(3) - 8 = 428 . Thus, the remainder is 428 when dividing by x - 3.

#SPJ5

The answer is 3072 cm².

Lateral surface area of a pyramid can be expressed as:

L = P × l

where:

L - Lateral surface area

P - Perimeter of a base

l - slant height

We have:

L = ?

P = ?

l = 24 cm

a = 32 cm

Perimeter of a base which is a square is:

P = 4 × a

P = 4 × 32 cm

P = 128 cm

Thus,

L = P × l

L = 128 cm × 24 cm

L = 3072 cm²

Therefore, the lateral surface area is 3072 cm².

Lateral surface area of a pyramid can be expressed as:

L = P × l

where:

L - Lateral surface area

P - Perimeter of a base

l - slant height

We have:

L = ?

P = ?

l = 24 cm

a = 32 cm

Perimeter of a base which is a square is:

P = 4 × a

P = 4 × 32 cm

P = 128 cm

Thus,

L = P × l

L = 128 cm × 24 cm

L = 3072 cm²

Therefore, the lateral surface area is 3072 cm².

**Answer:**

1536

**Step-by-step explanation:**

$540 dollars because 9times 60